2021
DOI: 10.1134/s1024856021040035
|View full text |Cite
|
Sign up to set email alerts
|

Surface Ozone Concentration in Russia in the Second Half of 2020

Abstract: We present information on ozone concentration in the surface air layer in the second half of 2020. Data were obtained at 13 stations located in different regions of Russia. We estimated the excess over hygienic standards of the Russian Federation, both in the second half of the year and throughout 2020. It is shown that the daily average maximum permissible concentration of ozone is regularly exceeded at all stations. There are cases of exceeding the one-time maximum permissible concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
5
1
1
Order By: Relevance
“…Third, in the development of a summertime maximum that became the primary maximum in the annual behavior of surface ozone [ 52 – 54 ]. This markedly differs from data presented in previous reviews [ 29 , 30 ]. In 2020, the weather in Moscow, which was rainier and colder than usual, was accompanied by decreased ozone concentrations, a poorly defined springtime maximum, and the absence of a summertime maximum.…”
Section: Measurement Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…Third, in the development of a summertime maximum that became the primary maximum in the annual behavior of surface ozone [ 52 – 54 ]. This markedly differs from data presented in previous reviews [ 29 , 30 ]. In 2020, the weather in Moscow, which was rainier and colder than usual, was accompanied by decreased ozone concentrations, a poorly defined springtime maximum, and the absence of a summertime maximum.…”
Section: Measurement Resultscontrasting
confidence: 99%
“…It should be noted that, like previous half-year reviews in 2020 [ 29 , 30 ], 2021 coincided with the period of coronavirus pandemic and, as such, can reflect the lockdown results. The meta-analysis carried out in [ 31 33 ] using monitoring at tens of stations around the globe showed that reduction of emissions of the main admixtures was usually accompanied by the growth of ozone concentration in the surface air layer.…”
Section: Introductionmentioning
confidence: 52%
See 2 more Smart Citations
“…Для анализа нами были использованы официальные данные по частоте ежедневной заражаемости и смертности от COVID-19 в Москве в 2020-2021 годах, публикуемые Роспотребнадзором [19]. Данные по содержанию озона в приземном слое атмосферы Москвы были получены нами в результате измерений, проводимых в нашей лаборатории мониторинга качества атмосферы Российского университета дружбы народов [20,21]. Автоматическая станция мониторинга расположена в центре Москвы, в пределах третьего транспортного кольца, по адресу: ул.…”
Section: материалы и методыunclassified